ISOLATION AND BIOCHEMICAL CHARACTERIZATION OF CANIS LUPUS FAMILIARIS AND HUMAN SALIVA AGAINST THE PATHOGENIC BACTERIA AND ANALYSIS OF ANTIMICROBIAL ACTIVITY - Sahu, Ajay Kumar; Paramita, Prangya; Swain, Akash; Pallath, Karthika S; Sinha, Rupali; Soni, Abhisek (Asian Journal of Pharmaceutical Research and Development, 2019)
Saliva is mainly contain protein have an important role biological system of that oral cavity is closely associated with different type of disease, in our research work we took canis lupus familiaris saliva which because the composition of dog salivary proteome and with relationship with human are unclear. Salivary proteome have more than 2353 differentially expressed protein human and dog salivary. Protein related regeneration and healing process as fibroblast growth factor and epidermal growth factors regulated by dog salivary, animal saliva is also known as common source of allergen. The main of this study and research work was to identify the particular species and determine the prevalence of pathogenic bacteria in the saliva of canis lupus familiaris, the biochemical analysis is used to to identify the particular kind of bacteria was present in dog saliva and how its access to another bacteria through antimicrobial activity test was done. Canine saliva was tested for bacterial effect against pathogens relevant to the hygienic function of maternal grooming of the mammary. Bactericidal against coagulase positive staphylococcus and pseudomonas, e coli is the cause of highly fatal coliform enteritis of mammal. The oral proteomes of dog and human were appreciably different most probably cellular process, development process, multi cellular process, metabolic process, immune system process, biological adhesion is different according to the their biological appearance. These research work provide new information on canis lupus familiaris saliva composition and which type of bacteria is present it, and how will be beneficial for the study of dog saliva in diseased and health condition in future.